NATURE OF COUPLING BETWEEN NUCLEUS AND ELECTRONS IN THE FORMATION AND STABILITY OF ATOMS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In order to explain observed exceptional stability of atoms and discreet line spectra of elements, Bohr postulated the existence of statutory orbits in which electrons are supposed to move around the nucleus, without emission of electromagnetic radiation as demanded by classical electrodynamics, but counterbalancing the pull towards the nucleus due to coulomb attraction by the centrifugal force in agreement with classical mechanics. The apparent anomaly in rejecting the result of classical electrodynamics, but retaining the principle of classical mechanics in Bohr’s Postulate of so called stationary orbits can be traced to the assumption that only forces of electrical attraction operate between positively charged protons in the nucleus and the negatively charged electrons outside it. Due to such assumption, there arose the need to postulate the operation of equal and opposite centrifugal forces due to motion of electrons in agreement with the laws of classical mechanics, counter balancing coulomb attraction towards the nucleus and at the same time, not to obey the result of classical electrodynamics which predicts loss of energy by an accelerated electron which would result in motion of electron along spiral trajectory with decreasing radius ultimately leading to the collapse of the atom.